2004
DOI: 10.1016/j.bbamcr.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tenascin-C by cyclic tensile strain versus growth factors: distinct contributions by Rho/ROCK and MAPK signaling pathways

Abstract: Expression of the extracellular matrix (ECM) protein tenascin-C is induced in fibroblasts by growth factors as well as by tensile strain. Mechanical stress can act on gene regulation directly, or indirectly via the paracrine release of soluble factors by the stimulated cells. To distinguish between these possibilities for tenascin-C, we asked whether cyclic tensile strain and soluble factors, respectively, induced its mRNA via related or separate mechanisms. When cyclic strain was applied to chick embryo fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 43 publications
1
81
1
Order By: Relevance
“…1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity. 5 Similarly human cutaneous SCCs demonstrated ROCK2/p-Mypt1 staining correlated with MLC2 phosphorylation and actomyosin contractility; 6 suggesting a mechano-transduction pathway facilitated progression by providing the mobility/flexibility necessary to invade tissues with increased rigidity, [6][7][8] ideas supported by analysis of tenascin C [28][29][30] and p-Mypt1 inactivation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity. 5 Similarly human cutaneous SCCs demonstrated ROCK2/p-Mypt1 staining correlated with MLC2 phosphorylation and actomyosin contractility; 6 suggesting a mechano-transduction pathway facilitated progression by providing the mobility/flexibility necessary to invade tissues with increased rigidity, [6][7][8] ideas supported by analysis of tenascin C [28][29][30] and p-Mypt1 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Tenascin C is a large ECM/molecule associated with alterations in rigidity that drive progression [27][28][29] and previously linked with activated Rho/Rock and MAP Kinase signalling. 28,29 Tenascin C expression reflects tumour aggression and metastatic potential 27,[48][49][50] and also associated with deregulated NF-κβ signalling 48 and NF-κβ roles in inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanoregulation of gene expression has been widely studied in chicken skin fibroblasts, and various mechanisms have been proposed for the mechanoregulation of ECM genes (Chiquet-Ehrismann et al, 1994;Chiquet et al, 1996Chiquet et al, , 2003Chiquet et al, , 2004Sarasa-Renedo and Chiquet, 2005;Sarasa-Renedo et al, in press). The genes of focus in these studies are tenascin-C and collagen fibril-associated type XII collagen.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%
“…The resulting increase in force at focal complexes triggers the transition of these structures into focal contacts. It has been shown that ROCK inhibitor attenuates cyclic stretching-mediated tenascin-C mRNA induction, and ROCK stimulators act synergistically with cyclic stretching to induce tenascin-C, suggesting a direct correlation between the tenascin-C gene induction and ROCK-mediated cytoskeletal tension (Chiquet et al, 2004;Sarasa-Renedo et al, in press). …”
Section: Cellular Mechanotransductionmentioning
confidence: 99%